2010
DOI: 10.1007/978-3-642-13119-6_30
|View full text |Cite
|
Sign up to set email alerts
|

Strategy-Proof Dynamic Resource Pricing of Multiple Resource Types on Federated Clouds

Abstract: Abstract. There is growing interest in large-scale resource sharing with emerging architectures such as cloud computing, where globally distributed and commoditized resources can be shared and traded. Federated clouds, a topic of recent interest, aims to integrate different types of cloud resources from different providers, to increase scalability and reliability. In federated clouds, users are rational and maximize their own interest when consuming and contributing shared resources, while globally distributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Similarly, offer type is also defined by the sender based in Alternate Offers operations. and strategy-proof negotiation [21] can be supported by the Cloud Coordinator if the negotiation Engine is extended with these extra functionalities or if a new Negotiation Engine, supporting such features, replaces the one described in this section.…”
Section: Negotiation Enginementioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, offer type is also defined by the sender based in Alternate Offers operations. and strategy-proof negotiation [21] can be supported by the Cloud Coordinator if the negotiation Engine is extended with these extra functionalities or if a new Negotiation Engine, supporting such features, replaces the one described in this section.…”
Section: Negotiation Enginementioning
confidence: 92%
“…Works related to systems for market-making such as GridEcon [18], SORMA [19], and Mandi [5], as well as the works by Song et al [20], Mihailescu and Teo [21], Gomes et al [22], and Vanmechelen et al [23] concern mechanisms for creating markets, trading resources (e.g., auctions or fixed price), and also mechanisms to motivate market maintenance, i.e., study and development of techniques that motivate both resource providers and resource consumers to join and stay in the market.…”
Section: Markets For Computing Resourcesmentioning
confidence: 98%
“…The business aspect of service migration is not studied in depth. In [22] a pricing model is proposed for multiple types of shared resources in a federated Cloud, but it only focuses on the study of the allocation of shared resources joining the federated Cloud. Open Cirrus [23] is a global Cloud computing test bed which federates 10 distributed data centers across North America, Europe and Asia.…”
Section: Other Related Work In Federated Cloudmentioning
confidence: 99%
“…Although simple to implement, fixed pricing is not suitable for a system with multiple providers, or where users are both sellers and buyers of resources [13]. Federated clouds, a topic of recent interest, aims to integrate cloud resources from different providers, to increase scalability and reliability [4].…”
Section: Related Workmentioning
confidence: 99%
“…For simplicity, we have considered a centralized marketmaker that manages the available resources and requests. However, our results have shown that scalability becomes an issue when the number of users or the number of resource types is increased [13]. In this paper, we focus on resource location and propose a scalable, distributed market framework.…”
Section: Proposed Distributed Market Architecturementioning
confidence: 99%